Use of antibiotics in renal failure: need for dose adjustments and individualized doses (Research, Society and Development, 2020)
Pharmacokinetic and pharmacodynamic changes in medicinal products due to impaired renal function are frequently observed. According to the World Health Organization -WHO (2015), it is possible to lose up to 90% of renal function before manifesting any symptoms. The aim of this study was to create a practical table for consultation of antibiotics that need adjustment in patients with renal failure. A documentary, descriptive and analytical study with a qualitative approach was performed based on the pharmacokinetic analysis of standardized antibiotics at the University Hospital of Piaui, seeking to identify the need for dose adjustments and frequency of use according to the renal function of the patient. For the execution of the study, references described in package inserts for health professionals were consulted, and the information compared to references described in pharmacotherapeutic guides of the main excellence hospitals in Brazil and the Standford guide, as well as literature reviews. Antimicrobials were organized by pharmacological class, describing dose adjustment depending on creatine clearance and supplemental dose after hemodialysis. Despite the guidelines regarding dosage adjustment in patients with renal failure, there are still doubts, as there are other factors that influence this correction such as the dialysis method used in hemodialysis that includes: intermittent or conventional, ultrafiltration, low efficiency dialysis. The present study generated a quick consultation table to clarify doubts in the prescription or dispensation of standardized antimicrobials in the hospital, thus promoting safer and more efficient antimicrobial therapy.